Bullous Pemphigoid in Patients Receiving Immune-Checkpoint Inhibitors and Psoriatic Patients-Focus on Clinical and Histopathological Variation - Dennis Niebel; Dagmar Wilsmann-Theis; Thomas Bieber; Mark Berneburg; Joerg Wenzel; Christine Braegelmann (MDPI AG, 2022)
Background: The most common autoimmune blistering disease, bullous pemphigoid (BP), shows an increased prevalence in psoriatic patients and oncologic patients undergoing immune-checkpoint blockade (ICB). Even though the same autoantigens (BP180/BP230) are detectable, it remains obscure whether clinical or histopathological differences exist between these different groups of BP patients. In this study, we strived to analyze this matter based on own data and previously published reports. Methods: We performed an institutional chart review from 2010-2020 to identify BP patients with psoriasis (n = 6) or underlying ICB (n = 4) and matched them with idiopathic cases of BP (n = 33). We compared clinical characteristics, subtypes, and dermatopathological determinants (e.g., tissue eosinophilia/neutrophilia, papillary edema, lymphocytic infiltration) among the groups. Results: ICB-associated BP affects men more often and might show mucosal involvement more frequently. We found no statistically significant dermatopathological differences among the groups. Conclusions: Clinicians should be aware of an increased risk of BP in patients with psoriasis and oncologic patients receiving ICB; atypical pruritic skin lesions should prompt a workup including a skin biopsy for histopathology and direct immunofluorescence in these patients. Larger studies might be necessary to detect slight dermatopathological variation.